Teachers’ Experiences and Students’ Responses to Digital Platforms in Online English Learning - Ruwandi Ruwandi; Alfatihah Dwi Pangestu; Nafian Rahma Fitriyani; Devi Silvia (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Digital platforms have become an important component in supporting English language learning beyond emergency situations. However, most previous studies focus on pandemic-based online learning, leaving limited insights into non-emergency contexts. This study aims to explore teachers’ experiences and students’ responses to digital platforms used in online English learning during a school renovation period at SMA Negeri 1 Getasan. A qualitative case study design was employed, involving English teachers and five eleventh-grade students selected through purposive sampling. Data were collected through observation, interviews, and document analysis, and analyzed using Miles and Huberman’s interactive model with source triangulation. The findings reveal that Google Classroom and WhatsApp were effective for material delivery and task management, while interactive platforms supported engagement. Nevertheless, challenges emerged related to student motivation, limited interaction, and assessment authenticity. The study concludes that digital platforms are best implemented as complementary tools within a blended learning model rather than as a full replacement for face-to-face instruction.